Therapeutic strategies for preventing skeletal muscle fibrosis after injury - Garg, Koyal; Corona, Benjamin T.; Walters, Thomas J. (Frontiers in Pharmacology, 2015)
Skeletal muscle repair after injury includes a complex and well-coordinated regenerative response. However, fibrosis often manifest, leading to aberrant regeneration and incomplete functional recovery. Research efforts have focused on the use of anti-fibrotic agents aimed at reducing the fibrotic response and improving functional recovery. While there are a number of mediators involved in the development of post-injury fibrosis, TGF-β1 is the primary pro-fibrogenic growth factor and the preponderance of research has focused on reducing its impact. The majority of these studies have shown that this strategy is effective in improving muscle healing following most common forms of muscle injuries. A number of these agents are FDA approved for other indications, clearing the way for rapid translation into clinical treatment. However all have potential side effects that must be considered in weighing the cost-benefit of the treatment require continued animal and clinical research.